Nonalcoholic Steatohepatits and Liver Steatosis Modify Partial Hepatectomy Recovery. (1st February 2015) - Hoppe, Steffi; von Loeffelholz, Christian; Lock, Johan F.; Doecke, Stephanie; Sinn, Bruno V.; Rieger, Anja; Malinowski, Maciej; Pfeiffer, Andreas F. H.; Neuhaus, Peter; Stockmann, Martin
ABSTRACT Background: The impact of nonalcoholic fatty liver disease (NAFLD) comprising simple steatosis (NAFL) and steatohepatitis (NASH) on liver recovery after partial hepatectomy has not been evaluated. This pilot study investigated whether there is an effect of proven NAFLD on liver recovery. Methods: Thirty-one patients elected for partial hepatectomy were characterized and included into a prospective study. Liver samples were staged according to the NAFLD activity score. Liver function was measured by using the LiMAx method on postoperative days (POD) 1, 3, 5, and 10. Results: Nineteen patients were identified to suffer from NAFLD (NAFL, n = 11; NASH, n = 8). In NAFL, preoperative liver function (p = .48) and hepatic recovery on POD 1, 3, and 5 was comparable to controls (p > .05, respectively), while it was impaired on POD 10 (p = .022). NASH patients had preoperative enzymatic function comparable to controls (p = .10), but there was a trend to reduced levels on POD 1 (p = .082) and 5 (p = .062), which became significant on POD 10 (p = .003). Conclusion: This study suggests that NAFLD impairs functional recovery assessed by LiMAx after partial hepatectomy.